The Effect of Anemia with Iron Tanks on the Fetal Female Body (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Many health features of a pregnant woman have an impact on the condition of the fetus and subsequently the newborn. Iron deficiency anemia is the most frequently detected pathology during pregnancy, which not only worsens a woman's quality of life, but can also negatively affect the condition of the fetus. Due to iron deficiency, adverse pregnancy outcomes have been described in the literature, a number of which have been reliably confirmed. Timely detection and effective therapy of iron deficiency anemia in pregnant women can prevent the development of complications and thereby improve pregnancy outcomes.